DETECTION, DIAGNOSTICS AND CLINICAL MANIFESTATIONS OF TUBERCULOSIS IN HIV-INFECTED CHILDREN - E. B. Vаsilyevа; M. E. Lozovskаya; L. V. Klochkovа; Yu. A. Yarovаya (Туберкулез и болезни лёгких)
About 90% of HIV positive women are of the reproductive age, which results in the higher number children with perinatal exposure to HIV. Subjects and Methods. Data of case histories of 20 children with TB/HIV co-infection and 30 HIV negative children with tuberculosis were analyzed. Certain cases of late diagnostics of HIV with perinatal exposure to HIV were found. Tuberculosis was more detected in children with HIV infection based on clinical signs compared to children with HIV negative status (in 25 and 5% cases respectively). More than one third (35%) of patients with TB/HIV co-infection had a negative sensitivity to tuberculin and 50% of patients responded negatively to diaskintest.